The Effect of Talent Management on Employee Performance with Self-Efficacy as Mediation Variables - Sinta Marhuri; Okta Karneli (Almana : Jurnal Manajemen dan Bisnis, 2023)
In the current era of globalization and economic growth, every organization needs to survive in competition with other organizations. One of the strategies to win this talent war is to implement talent management, which is used to identify, find, develop, manage, and retain talented employees to achieve strategic goals and meet future business needs. The purpose of this study was to determine the effect of talent management on employee performance using self-efficacy as a moderator variable. Talent management is the independent variable (X), self-efficacy is the intervening variable (Z), and employee performance is the dependent variable (Y). The methods used in this research are descriptive and quantitative statistics. The sample for this study was taken from as many as 65 respondents from the total population using the census/total sampling method. The data obtained from the results of the questionnaire were tested statistically through the Warp PLS 7.0 program. The results of the tests conducted show that talent management has a positive and significant effect on employee performance, talent management has a positive and significant effect on self-efficacy, self-efficacy has a positive and significant effect on employee performance, and talent management has a positive and significant effect on employee performance through self-efficacy.